Effective Systemic Treatment of Choroidal Metastases NSCLC With Surgery After Crizotinib: A Case Report - Liu, Shilan; Liu, Xiao; Wang, Ting; Zeng, Chunhua; Ren, Baichen; Yu, Xiaodan; Xu, Min; Li, Wenjuan; Qiao, Zhihui; You, Chuanyun; Yang, Qinghui; Chen, Mei (Frontiers in Oncology, 2022)
Choroidal metastasis as an initial presenting feature of lung cancer with EML4-ALK translocation is exceedingly rare and greatly impacts patient quality of life (QOL) (1). There are no recommended treatments for such patients, and palliative care remain limited (2). It is unclear whether surgical resection of primary pulmonary lesions, systemic antitumor therapy, targeted therapy, or localized ocular therapy are effective in treating choroidal oligometastases of lung cancer with EML4-ALK translocation. Here, we present the case of choroidal metastases secondary to lung cancer and EML4-ALK translocation in a 57-year-old woman who firstly underwent resection of lung lesions and oral administration of crizotinib without local treatment or systemic chemotherapy. Fortunately, she had a rapid and complete response to crizotinib with 27 months of progression-free survival.